ترشيد النفقات العمومية - صالحي ،حنان; لطيف ،وليد (جامعة الوادي University of Eloued, 2025)
Aims This is amazing Study toConducting a bibliometric analysis of 785 publicationsAscientificAlisted in databaseScopus, during the period from 1949 to 2023. The analysis focuses on the development of scientific publishing, patterns of cooperation between research institutions,And the countries, and the recurring relationships between keywords, using the program VOSviewer. The results of the study showed that the topic under investigation dates back to an ancient period of time, but research interest in it has begun to increase significantly in recent decades.But at a relatively slow pace of growth. In terms of impact, the authorBirrell.DHe is the most published author, while the author occupiesHowlett.MRanked first by importance of publications, the United States leads in number of publications with a total of four institutions.
Rationalization of public expenditures: a bibliometric study for the period 1949-2023
Keywords: ترشيد النفقات; الحكومة; التحليل الببليومتري; التحليل المشترك; Rationalization of expenditures; government; bibliometric analysis; joint Analysis; program VOSviewer